HSN7038: Perspectives of Family Centred Health & Social Care (2211_SPR) - Btihal Ibraheem Alnaimi (British Journal of Healthcare and Medical Research, 2023)
Family-Centred Care (FCC) represents a structure that offers enhanced healthcare decision-making as a result of enhanced collaboration and information between families and professional healthcare providers. Achieving this requires training, education, and support, which would ensure that all healthcare providers and staff have a shared understanding of FCC practices. The various healthcare service providers and institutions within a single geographical zone can participate in this program to improve the level of cooperation between them.‎ Therefore, this paper conducts a critical examination of the FCC approach with a particular emphasis on the way the FCC influences the practice in Paediatric Intensive Care Units (PICU). Families are central to children’s lives and FCC is an approach that recognizes this fact; thus, allowing families to engage in their children’s treatment on an equal footing and ensuring the best possible results for children, families, and the institutions providing care. Along with a review of this field’s studies, this paper discusses the way the FCC theory came to be developed and the reason behind its significance. This paper also refers to a case study to better understand the way to effectively apply FCC in practice while avoiding the obstacles that may arise.